The Role of Colostrum for Passive Immunity Transfer in Newborn Calf - Henderiana L.L Belli (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2009)
The neonatal immune system at birth is naive to the wide variety and types of pathogen present in the environment. Consumption of colostrum to provide circulating IgG prior to the cessation of macromolecular transport (“closure”) is essential to ensure the healthiness of the calves. There are many factors that may influence the absorption of immunoglobulin G (IgG) by calves from their mothers as passive immunity, including the timing of colostrum intake. The earliest colostrum intake within 6 hours after birth is primarily important, when the colostrum’s value is the most complete from biological point of view i.e. high titre of Ig, high lysozyme, bactericidal and growth factors. Igs are absorbed by small intestine mucosa by pinocytosis for a relative short time (8 – 12 hours), then, the permeability of intestinal mucosa in calves strongly decreases and becomes entirely impermeable after 24 hours. Successful transfer of passive immunity has been determined by measuring the concentration of IgG in the serum of the calf at 24 to 48 hours after birth. The critical level for determining failure of passive transfer of immunity (FPT) is usually considered at 10 g/l. Calves with less than 10 g/l of serum IgG are at high risk of diseases than calves with higher serum IgG concentration. There are many factors that influence the concentration of IgG in the blood of the calf at the age of 24 to 48 hours, including apparent efficiency of IgG absorption (AEA).   Key words: Colostrum, immunoglobulin, neonatal, intestinal closure